Philippine construction directory, 1997. (Makati City Pacific Trade Media Publications, 1997)
This directory is intended to guide consumers as regards the need for professional services offered by architects, civil engineers and interior designers. Names/addresses/contact numbers of government offices, suppliers, contractors and developers are included as well. It also contains a section called buyer's guide and an advertisers' index. It is alphabetically arranged by section.
A directory of Philippine construction agents and companies on the year 1996. It is divided into six sections which are separated by colored tabs: government, professionals, supplies, buyer's guide, contractors, and developers.
Cover title.
Keywords: Construction industry -- Philippines -- Directories